Empowering Women’s Educational Journeys: Navigating Challenges in Pursuit of Higher Education in Dera Ghazi Khan - Habib, Musarrat; Ejaz, Laiba; Alvi, Gulshan Fatima (Journal of Development and Social Sciences, 2024)
The present study examined the challenges faced by female students in accessing higher education in Dera Ghazi Khan, a marginalised region in Punjab, Pakistan. In such underprivileged areas, women encounter significant barriers, including social, cultural, financial, gender-related, and infrastructural impediments. Employing a mixed-methods research approach, we surveyed 450 students and conducted interviews with 13 teachers from female colleges in Dera Ghazi Khan, selected through a multi-stage sampling technique. Quantitative analysis revealed that early marriage, traditional customs, restricted mobility, rural living, and economic constraints significantly obstruct female education. Thematic analysis of teacher interviews highlighted societal norms and the perception of female education as less valuable than male education. Additional challenges include a shortage of educational institutions and teachers, transportation issues, and a lack of awareness about higher education opportunities. The study recommends increasing scholarships, improving transportation, creating job opportunities, and raising awareness to enhance female education in the region.